Budesonide MMX® for the induction of remission of mild to moderate ulcerative colitis: a pooled safety analysis. - Lichtenstein, G; Travis, S; Danese, S; D'Haens, G; Moro, L; Jones, R; Huang, M; Ballard, E; Bagin, R; Hardiman, Y; Collazo, R; Sandborn, W (Oxford University Press, 2015)
BACKGROUND AND AIMS: Cumulative safety and tolerability of budesonide MMX(®), a once-daily oral corticosteroid for inducing mild to moderate ulcerative colitis remission, was examined. METHODS: Data from three randomized, double-blind, placebo-controlled, phase II or III studies (budesonide MMX 9 mg, 6 mg, or 3 mg for 8 weeks); one phase II study (randomization to budesonide MMX 9 mg or placebo for 4 weeks, then open-label budesonide MMX 9 mg for 4 weeks); and one open-label study (budesonide MMX 9 mg for 8 weeks) were pooled. RESULTS: Patients randomized to budesonide MMX 9 mg (n = 288), 6 mg (n = 254), or placebo (n = 293) had similar rates of adverse events (AEs) (27.1%, 24.8%, and 23.9%) and serious AEs (2.4%, 2.0%, and 2.7%); treatment-related AEs and serious AEs were reported by 11.8% and 13.5%, and 5.9% and 2.2%, respectively, of patients receiving budesonide MMX 3 mg (n = 17) or open-label budesonide MMX 9 mg (n = 89). Mean morning plasma cortisol concentrations were normal from baseline to final visit across randomized groups; in patients receiving open-label budesonide, mean cortisol concentration was 129.9 nmol/l after 4 weeks, returning to normal concentrations at final visit. Budesonide MMX was not associated with an overall increased risk for glucocorticoid-related adverse effects. CONCLUSIONS: Budesonide MMX 9 mg was associated with normal mean cortisol concentrations at final visit and an AE incidence comparable to placebo. Overall, budesonide MMX was safe and well tolerated for inducing remission of patients with mild to moderate ulcerative colitis.